2002
DOI: 10.18785/goms.2001.05
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Model Calculation of the Flow in DeSoto Canyon in Response to Northerly Wind Bursts in Winter

Abstract: The continental shelf currents observed at the head of DeSoto Canyon offshore of Pensacola, FL, during Nov, 1997-Feb. 1998, are studied with the aid of a Bryan-Cox model of the entire Gulf of Mexico. The basic model circulation with no winds features a Loop Current and a weak flow in DeSoto Canyon. In contrast, the model response to northerly wind bursts produces strong canyon currents. Wind-driven southward currents on the West Florida Shelf (WFS) appear to pull a strong flow around DeSoto Canyon, giving rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Weaker mean flow occurred over the middle of the MBS, eastern portions of the domain, and the southeastern DCH region. In general, the HF radar velocities are in agreement with previous work on circulation in the region [ He and Weisberg , , ; Hsueh and Golubev , ; Smith and Jacobs , ; Wang et al ., ; Weisberg et al ., ; Yuan , ] although these studies generally found jet‐like surface flow to exit the region toward the southeast following the 100 m isobath. Daily mean flow patterns (not shown), along with mean flow for June 2010 (Figure ), reflect Ekman transport dynamics by exhibiting flow to the right of the wind direction.…”
Section: Observations and Resultssupporting
confidence: 90%
“…Weaker mean flow occurred over the middle of the MBS, eastern portions of the domain, and the southeastern DCH region. In general, the HF radar velocities are in agreement with previous work on circulation in the region [ He and Weisberg , , ; Hsueh and Golubev , ; Smith and Jacobs , ; Wang et al ., ; Weisberg et al ., ; Yuan , ] although these studies generally found jet‐like surface flow to exit the region toward the southeast following the 100 m isobath. Daily mean flow patterns (not shown), along with mean flow for June 2010 (Figure ), reflect Ekman transport dynamics by exhibiting flow to the right of the wind direction.…”
Section: Observations and Resultssupporting
confidence: 90%
“…Statistics on the complete dataset shows a small improvement over shelf areas, as in Liu et al (2014), but it is not significant given the high variability. The physical reason for this result is most likely due to the fact that in our region of interest the dynamics are mostly influenced by mesoscale and/or submesoscale processes (Poje et al 2014), for which wind action cannot be simply described as a superposition between geostrophic and Ekman flow (Nowling et al 2000;Hsueh and Golubev 2002;Hamilton and Lee 2005;Clarke and VanGorder 2013;Kourafalou and Androulidakis 2013).…”
Section: October 2015 B E R T a E T A Lmentioning
confidence: 96%
“…2). On the other hand, on the shelf and DeSoto Canyon, where the action of the wind is potentially more significant, the superposition of the Ekman component on geostrophic currents does not take into account the complex response to changes in wind forcing in terms of time scales (Stewart 2008;Sudre and Morrow 2008) as well as several other processes contributing to the surface current dynamics, such as the eddy-induced shelf break and slope circulation (Ohlmann et al 2001;Wang et al 2003;Hamilton and Lee 2005), river discharges (mainly Mississippi and Apalachicola) (Schiller et al 2011;Kourafalou and Androulidakis 2013), upwelling events (Nowling et al 2000;Hsueh and Golubev 2002), wind-driven currents from the west Florida shelf (Yuan 2002;Clarke and VanGorder 2013), and the submesoscale-induced transport (Poje et al 2014).…”
Section: B Aviso-ncepmentioning
confidence: 99%
“…However, their influence on the coastal zones is limited due to the width of the shelf (Marmorino, 1982). The greatest influence of ambient background currents comes from flow reversals which are related to the Northerly winds from CAO's (Mitchum and Clarke, 1986;Hsueh and Golubev, 2002). Roth (2016) describes the full depth flow reversals -flow to the West under winds to the North before frontal passage reversing to flow to the East under winds to the South after frontal passage -as an ageostrophic response to wind driven setup / setdown and finds a variation of alongshore flow velocity of 0.3 m/s within 3 h.…”
Section: The Buoyant Plume Of the Choctawhatchee Bay As A Coastal Promentioning
confidence: 99%